Produção de concretos autoadensáveis com baixo consumo de cimento e sua influência na aderência aço-concreto - Barboza, Lucas da Silva (2018)
Self-compacting concrete (SCC) must simultaneously exhibit high fluidity, cohesion and absence of segregation. However, the maintenance of these properties in the fresh state requires a greater consumption of binders and additions, and consequently generating a cost increase in the manufacture of the concrete. In this context, the present work seeks to evaluate the feasibility of the production of Self-Adhesive Concretes with Low Cement Consumption (SCCLCC), determining their properties in the fresh and hardened state. Appropriate inputs for the CAABCC dosage were selected, characterized and the optimal voids index at the packaging step between the aggregates determined. Self-compacting concrete with reduced cement content, with high compressive strength and cement consumption indices of 4.50 to 5.45 kg / m³. MPa-1 at 28 days were reached, in which these values are below those obtained for this type of concrete. These results demonstrate that even under low cement content dosing conditions, the properties in the fresh and hardened state were maintained, thus not suffering significant losses in relation to the reference concrete. Therefore, the results indicate that SCCLCC production with the necessary flowability, satisfactory resistance and reduced cement consumption is feasible. This makes SCC more efficient, with significant cost reductions and environmental impact without compromising its properties.